2007
DOI: 10.1016/j.envres.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to volcanic environments and chronic bronchitis incidence in the Azores, Portugal

Abstract: The village of Furnas, like other active volcanic areas in the world, exhibits high levels of hazardous gases. We aimed to investigate the existence of a possible association between chronic exposure to volcanic sulfur gases and chronic bronchitis. To investigate this, we used two populations, one exposed to active manifestations of volcanism (Furnas) and another from an area where no volcanic activity took place for over three million years (Santa Maria), both in the Azores. We used data on the incidence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…The prevalence of chronic bronchitis-like symptoms defined by Based on a 10-yr follow-up observation in the Azores, Portugal, Amaral et al (2007) 10) reported a relationship between exposure to volcanic gases and the incidence of chronic bronchitis recorded at local health centers. Relative risks of chronic bronchitis in males and females exposed to volcanic gases were 3.99 (95% CI; 2.98-5.35) and 10.74 (6.55-17.34), respectively, compared to those living in volcanically inactive areas.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of chronic bronchitis-like symptoms defined by Based on a 10-yr follow-up observation in the Azores, Portugal, Amaral et al (2007) 10) reported a relationship between exposure to volcanic gases and the incidence of chronic bronchitis recorded at local health centers. Relative risks of chronic bronchitis in males and females exposed to volcanic gases were 3.99 (95% CI; 2.98-5.35) and 10.74 (6.55-17.34), respectively, compared to those living in volcanically inactive areas.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the high bioavailability of cadmium and zinc found in soil invertebrates from this area (Amaral et al 2006b), high incidence rates of some cancer types and chronic bronchitis has also been registered in local humans (Amaral et al 2006c;Amaral and Rodrigues 2007). In order to assess the exposure and effects to a mixture of trace metals in this area, domestic mice (Mus musculus L.) from several households were collected for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a 10-year follow up observation in the Azores, Portugal, Amaral et al . (2007) 7) reported a relationship between exposure to volcanic gases and the incidence of chronic bronchitis recorded at local health centers. Relative risks of chronic bronchitis in males and females exposed to volcanic gases were 3.99 (95%CI; 2.98-5.35) and 10.74 (6.55-17.34), respectively, as compared to those living in volcanically inactive areas.…”
Section: Discussionmentioning
confidence: 99%